Aplicação da abordagem lean no processo de desenvolvimento de produto em empresas industriais brasileiras - Pinheiro, Larissa Maria Prisco (Universidade Federal de São Carlos, 2013)
Given the movement of national and international competitions, the fast technological advances, the reduction in life cycle of products on the market and greater demands for quality and services associated with products, product development has established itself as one of the business processes key to the growth and survival of businesses of various industrial sectors and has, over the years, becoming a powerful source of competitiveness for companies from various sectors. Toyota has developed and uses a product development model considered extremely competitive, which helped make it the largest automobile manufacturer in the world. This model is called Lean Development and is a worldwide reference. The model uses lean concepts, derived from Lean Thinking, in the product development process. Studies in international scope are being conducted in order to characterize, evaluate and apply this model in other companies, either automotive market or others different markets. This Thesis presents the results obtained by a survey carried out in manufacturing companies located at Brazil. The population was defined like innovative companies with product development area in the investigated site and with Lean Manufacturing applied for at leats five years. It is presented a descriptive analysis of the companies analyzed and a factorial analysis, which reduces the research variables in four contextual factors of Lean Development. A cluster analysis of the factors identified by the factorial analysis was performed and four groups of companies were founded. The groups were classified in relation to the product development process, according to literature. The results show that 38.2% of surveyed sample applies lean concepts (principles and tools) in both production system and product development process and approximately a half of surveyed sample (46.9%) applies only lean principles in production system, but does not migrate these principles to product development process. However, these last companies are the ones with the best results in product development.
Keywords: Desenvolvimento de produtos; ESBC; Product development; Lean development; SBCE; Survey; ENGENHARIAS::ENGENHARIA DE PRODUCAO